Case report on fatal human rabies infection in central India - Kumar, Pratik; Domple, Vijay; Khakse, Gautam (International Journal Of Community Medicine And Public Health, 2021)
Rabies is a zoonotic disease that affects the central nervous system of mammals and has a high mortality rate. It is a viral disease that can be prevented by vaccination. Dogs are the leading cause of human rabies deaths, accounting for up to 99% of all human rabies transmissions. On 15th December 2019 an 8 years old male child was bitten by a stray dog outside of his house. The patient visited with his parents to a nearby primary health care center on same day where his wound was washed with water. He received first dose of anti-rabies vaccine and was referred to a tertiary care center for immunoglobulin because of a history of wound bleeding. They did not visit tertiary care center for immunoglobulin as advised. 15 days after exposure on 1st January 2021 the patient presented with unusual behavior like fear of water and tremor. On examination his pupils were found dilated and he was referred to isolation ward of tertiary care center. Based on the history of animal bites and clinical signs, the patient was diagnosed as probable case of rabies. The patient eventually died within 24 hours of admission. Such kind of incident shows that there is lack of awareness regarding rabies in community. In this case, if the patient had completed the anti-rabies vaccination schedule and visited a higher centre on time for immunoglobulin, death could have been avoided. Mortality due to rabies can be prevented by raising public awareness about immunization.